Last chance Harvey - Perell, Tim.; Usborne, Nicola; Hopkins, Joel.; Hoffman, Dustin, 1937-; Thompson, Emma.; Atkins, Eileen, 1934-; Baker, Kathy, 1950-; Brolin, James, 1940-; Schiff, Richard, 1959-; Hinchliffe, Dickon; Overture Films; Process Media (Firm); et al. (2009)
Harvey, a divorced, down-on-his-luck music jingle composer, and Kate, a lonely British airline employee, are brought together by chance. Harvey comes to London for his daughter's wedding, planning only to attend the wedding ceremony. However, he ends up being let go from his job before going back to America and decides to stay for the reception, asking Kate to accompany him. Thus begins a growing connection between these two guarded strangers.
Title from container.
Originally released as a motion picture in 2008.
Director of photography, John de Borman ; editor, Robin Sales ; music, Dickon Hinchliffe.
Dustin Hoffman, Emma Thompson, Eileen Atkins, Kathy Baker, James Brolin, Richard Schiff.
PG.
DVD, region 3.
Keywords: Composers -- Drama; Jingles (Advertising songs) -- Drama; Flight attendants -- England -- London -- Drama; Fathers and daughters -- England -- London -- Drama; Marriage customs and rites -- England -- London -- Drama; Man-woman relationships -- England -- London -- Drama; London (England) -- Drama; Feature films